Adapted interfaces in magnesium alloys for biomedical applications: Synthesis, properties, and performance enhancement - Hashmi, Abdul Wahab; Tian, Yebing; Wang, Chunjin; Wang, Dazhong; Sagbas, Binnur; Puerta, Ana Pilar Valerga; Sankar, Mamilla Ravi (ELSEVIER SCIENCE SA, 2025)
Magnesium (Mg) alloys are promising biodegradable materials for biomedical implants because of the density (1.74-2.0 g/cm(3)) and Young's modulus (41-45 GPa) mimetic of the bone. The issues of rapid corrosion (0.2-0.5 mm/year) and hydrogen evolution (>0.01 ml/cm(2)/day) continue to inhibit instant use. This review focuses on adapted interfaces that enhance the corrosion resistance, mechanics, and biofunctionality via alloying. The study shows that yield strength up to > 250 MPa with thermodynamic modelling can be achieved. Furthermore, surface modification (plasma electrolytic oxidation [PEO] restrict to <0.1 mm/year corrosion under conditions) is another way to achieve it. In addition, additive manufacturing (selective laser melting for porous scaffold with 200-500 mu m interconnectivity and tailored degradation profiles) can help modify the properties of metals. These yield potential improvements of 50-60 % in cell adhesion and 20-30 % in antimicrobial efficacy by means of Mg ion release. According to in vivo studies, there is up to a 35-45 % bone volume/ tissue volume at 12 weeks in rabbit models in ideal implantation conditions, 25 % better than Ti controls. Yet, issues like scalability, coating adhesion, and standardization persist. The next step is to use nanotechnology for responsive interfaces, optimized alloy design through computational modeling, and regulatory frameworks (e.g., FDA/CE approval) for clinical translation. As per this analysis, Mg alloys are capable of being used as advanced biomaterials. Also, it describes some innovative materials researchers have developed for biomedical applications.
Keywords: Magnesium alloys; Biodegradable materials; Interface engineering; Surface modification; Alloying strategies; Additive manufacturing; Corrosion resistance; Mechanical properties; CELL LUNG-CANCER; MG ALLOYS; IN-VITRO; IMPLANTS; CORROSION; COATINGS; CHEMOTHERAPY; STRENGTH; CAMRELIZUMAB; SUBSTITUTES; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering